A Three-Dimensional Simulation Model for Proton Exchange Membrane Fuel Cells with Conventional and Bimetallic Catalyst Layers - Stefanos Tzelepis; Kosmas A. Kavadias; George E. Marnellos (Energies, 2023)
A three-dimensional steady-state model has been developed to study the phenomena that occurs during Proton Exchange Membrane Fuel Cell’s (PEMFC) operation. Electrochemical and transport phenomena on both the anode and cathode sides were investigated. Particular emphasis has been given to the composition and structure of the catalyst layers (CLs), considering parameters such as the metal loading, the most effective specific metal surface, the agglomeration, and the particle size. In this context, two types of CLs were investigated. The first type concerns conventional CLs consisting of Pt/C, while the second type refers to bimetallic CLs consisting of Pt-Ru/C. In both cases, the CLs were examined for various loadings of Pt, Ru, and C to define the optimum atomic ratio for an enhanced PEMFC performance, while, in parallel, possible challenges are intedified. The mathematical model for simulating the entire phenomena and the method for modeling the bimetallic catalyst layers are presented. The results show a good agreement between the model and the experimental data reported in the literature. Additionally, the scenario of bimetallic CLs consisting of Pt-Ru/C with a ratio of 50-50 (Pt-Ru) significantly improved the overall PEMFC electrochemical performance.